SISTEM JAMINAN SOSIAL DI MALAYSIA: SUATU TATAKELOLA PENYELENGGARAAN PER PROGRAM YANG BERBASIS PADA PELEMBAGAAN YANG TERPISAH - Purwoko, Bambang (L2Dikti Wilayah III, 2017)
Social security is a critical issue in the economy which functions as earnings substitute for all employees having loss of earnings due to sickness, work-accident, layoff, death and pension. Social security in Malaysia is managed separately in the operation since the first establishment in the 1950s seperate into 4 agencies consisting of employees provident tunds (EPF), social security organization (Socso), pension system for civil employees and armed force’s saving funds (AFSB). The objective of this research is to identify the operation of social security which keeps continued separately between private workers and public employees has reflected any good governance in the protection of working people. The methodology used in this study is descriptive method which focuses on review of ILO, ISSA concept and Malaysian system including the application of 5-principles of Good Corporate Governace GCG for the analysis of social security agencies as whether to be accepted universally in the globalization era. The conclusion of this study is that the operation of social security for the different status of members in Malaysia shall be separated, because of different financial sources between social security programs for private workers and public employees which indicate their different characteristics respectively.